2021
DOI: 10.1007/s10681-021-02941-6
|View full text |Cite
|
Sign up to set email alerts
|

Variation and genetic analysis of fatty acid composition in flax (Linum usitatissimum L.)

Abstract: Flax (Linum usitatissimum L.) is an important source of oil rich in omega–3 fatty acids (especially α-linolenic acid accounting for > 50%), which is proven to have health benefits and utilized as an industrial raw material. α-Linolenic acid is a polyunsaturated fatty acid that readily undergoes oxidative transformation. Autoxidation of α-linolenic acid is the principal process contributing to the development of off-flavors, loss of color, and alteration in the nutritional value of linseed oil. However, ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 39 publications
1
13
0
Order By: Relevance
“…Relatively high heritability values, ranging from 0.64 to 0.93 for agromorphological and seed quality traits, indicated that genetic variance predominates in total phenotypic variance and there is ample scope for improving these traits through selection (Saroj et al, 2021). This finding is in line with other studies that reported high heritability values for agro-morphological and seed quality traits in flax (You et al, 2017;Dabalo et al, 2020;Walkowiak et al, 2022).…”
Section: Discussionsupporting
confidence: 84%
“…Relatively high heritability values, ranging from 0.64 to 0.93 for agromorphological and seed quality traits, indicated that genetic variance predominates in total phenotypic variance and there is ample scope for improving these traits through selection (Saroj et al, 2021). This finding is in line with other studies that reported high heritability values for agro-morphological and seed quality traits in flax (You et al, 2017;Dabalo et al, 2020;Walkowiak et al, 2022).…”
Section: Discussionsupporting
confidence: 84%
“…Relatively high heritability values were calculated for agro‐morphological traits, ranging from 0.66 to 0.78 (Table 4) suggesting that additive gene effects were primarily responsible for the genetic variation in agro‐morphological and seed quality traits and there is high scope for the improvement of these traits through selection. Likewise, Soto‐Cerda et al (2014), Pali and Mehta (2014), You et al (2017), Dabalo et al (2020), and Walkowiak et al (2022) found high heritability estimates for these traits in linseed. Moderately high estimates of heritability (0.54–0.60) were observed for seed yield, aspartic acid content, moisture content, starch content, and ash content (Table 4).…”
Section: Resultsmentioning
confidence: 95%
“…Therefore, a selection procedure is considered as the best option for improving such traits through accumulating favorable alleles from parents with high GCA in the target genotype (Singh et al, 2019; Walkowiak et al, 2022). Previous studies also found that the contribution of additive effects in controlling the above traits was higher than the dominance component in linseed (Abdel‐Moneam, 2014; Delourme et al, 2006; El‐Kady & Abo‐Kaied, 2010; Singh et al, 2009; Sood et al, 2007; Walkowiak et al, 2022). The range of variation between the highest and lowest mean values for each trait was high that specifies a better scope of selection (Table 4).…”
Section: Resultsmentioning
confidence: 99%
“…Based on the classification and origin of the studied cultivars, their characteristics are presented in Table 1. The cultivars of flax used in our research were previously described by Walkowiak et al [15] and selected for the marker analysis. The two cultivars of flax Szafir and Oliwin have a very high α-linolenic acid content (>58%).…”
Section: Plant Materialsmentioning
confidence: 99%